INTERVENSI ANAK DALAM PERCERAIAN - Wahyudi, Firman (Pascasarjana UIN ANTASARI Banjarmasin, 2016)
The high divorce rate in Indonesia sometimes result with positive and negative trends. Positive trend meant the rise of women to defend their rights as a wife that is often abused by her husband so divorce is the best solutions and alternatives. Trend downside besides destroying a family structure also carries a psychological impact, especially children in addition to great effect in socio-civic life. Legal divorce just look at issues from both parties (husband and wife) only, while the other family members in this case the child is not involved. Though the realm of the family consisting of a husband and wife and children. Child has a fundamental right within the family and also have the right to intervene to prevent his parents divorce because he was the main victim of the divorce itself. Required a special advocate to defend the interests and rights of the child in his parents divorce given the level of skill in the legal act has not been adequate. In this case the role and functions of the Indonesian Child Protection Commission (KPAI) is necessary in order to fulfill these rights.